Doses de cama de aves e dejeto de suínos para sistema de integração lavoura-pecuária - Hentz, Paulo (2014)
This study aimed to determine the response of fertilization with doses of poultry litter and swine manure based on the nitrogen (N) for crop-livestock integration production system (SILP), demonstrated by carbon content in soil, dynamics Nitrogen (N), phosphorus (P) and potassium (K) in the soil-plant system,productivity of rye and corn, as well as the balance of nutrients through the years of 2011-2013. Experimental design occurred in randomized blocks, in the 4x4 factorial, repeated four times. The treatments consisted of four increasing doses of N (0, 100, 200 and 300 kg N ha-1) in interaction with four types of fertilizers, two of them were organic (poultry litter and swine slurry) and two balanced minerals with the same amounts of N, P and K as the organic ones, one related to swine manure - M1 and the other poultry litter - M2 in order to compare the dynamics of these nutrients from organic and mineral sources. The fertilization using organic fertilizers consisting of poultry litter and swine manure shows the same efficiency as the mineral one when adopted the same criteria for allocation of N, P and K in the cultivation system of corn and rye, with a direct relationship between the increase in N rates and productivity, nutrient availability in soil and absorption by plants, conditions that ensured the maintenance of soil fertility. The crop of rye BRS Serrano howed efficiency while absorbing N, P and K as winter pasture and due to the high productivity of upper area dry biomass it allows us to characterize it as a strategic cultivation for both removal and for nutrient cycling due the use of the forage being adopted as pasture, silage or ground cover on the production crop-livestock system integration. The high productivity of rye (22.1 t MS ha-1) and corn (24.7 t grain ha-1) through the agricultural years of 2011-2013 in SILP point to new higher standers for fertilizer recommendation, announcing amounts of 600 kg N ha-1, 109 kg of P ha-1 and 583 kg K ha-1 in the form of bedding and M2; 600 kg N, 59 kg P ha-1 and 441 kg K ha-1 as manure and M1, in the year where there was a higher productivity of both cultivations and it ensured a positive balance of nutrients in the SILP with three years of deployment